Cutting forces as a function of tool wear - Kovač, Pavel (Journal of Production Engineering, 1989)
This paper presents the experimental results of cutting forces and tool wear during face milling. Investigations have been performed with various values of cutting conditions, and a functional relationship between cutting forces and tool wear is presented.